Mycobacterial Infection of Precision-Cut Lung Slices Reveals Type 1 Interferon Pathway Is Locally Induced by Mycobacterium bovis but Not M. tuberculosis in a Cattle Breed - Remot, Aude; Carreras, Florence; Coupé, Anthony; Doz-Deblauwe, Émilie; Boschiroli, Maria L.; Browne, John A.; Marquant, Quentin; Descamps, Delphyne; Archer, Fabienne; Aseffa, Abraham; Germon, Pierre; Gordon, Stephen V.; et al. (Frontiers in Veterinary Science, 2021)
Tuberculosis exacts a terrible toll on human and animal health. While Mycobacterium tuberculosis (Mtb) is restricted to humans, Mycobacterium bovis (Mb) is present in a large range of mammalian hosts. In cattle, bovine TB (bTB) is a notifiable disease responsible for important economic losses in developed countries and underestimated zoonosis in the developing world. Early interactions that take place between mycobacteria and the lung tissue early after aerosol infection govern the outcome of the disease. In cattle, these early steps remain poorly characterized. The precision-cut lung slice (PCLS) model preserves the structure and cell diversity of the lung. We developed this model in cattle in order to study the early lung response to mycobacterial infection. In situ imaging of PCLS infected with fluorescent Mb revealed bacilli in the alveolar compartment, adjacent or inside alveolar macrophages (AMPs) and in close contact with pneumocytes. We analyzed the global transcriptional lung inflammation signature following infection of PCLS with Mb and Mtb in two French beef breeds: Blonde d’Aquitaine and Charolaise. Whereas lungs from the Blonde d’Aquitaine produced high levels of mediators of neutrophil and monocyte recruitment in response to infection, such signatures were not observed in the Charolaise in our study. In the Blonde d’Aquitaine lung, whereas the inflammatory response was highly induced by two Mb strains, AF2122 isolated from cattle in the UK and Mb3601 circulating in France, the response against two Mtb strains, H37Rv the reference laboratory strain and BTB1558 isolated from zebu in Ethiopia, was very low. Strikingly, the type I interferon pathway was only induced by Mb but not Mtb strains indicating that this pathway may be involved in mycobacterial virulence and host tropism. Hence, the PCLS model in cattle is a valuable tool to deepen our understanding of early interactions between lung host cells and mycobacteria. It revealed striking differences between cattle breeds and mycobacterial strains. This model could help deciphering biomarkers of resistance versus susceptibility to bTB in cattle as such information is still critically needed for bovine genetic selection programs and would greatly help the global effort to eradicate bTB.